The gender aspect of image formation in the modern information society - N. A. Yushkina (Цифровая социология)
The information space affects social processes and forms a new system of values, ideas about a person as a person, its self-expression and achievement of success in various areas of life. Image becomes an expression of new requirements of public consciousness. Based on the data of a sociological study, it has been identified and analyzed in the article: what value guidelines and qualities make up the image of the most authoritative representatives of modern Russian society, what is the gender composition of these representatives, as well as professional areas and qualities that help women gain a high level of trust and create a positive image in the modern information society.The factors, contributing to the formation of a negative image, have been considered, 329 interviews in 8 federal districts have been conducted. In the course of the interview, the respondents indicated the representatives of the society who, in their opinion, had the most positive image and high level of trust, as  well as the opposite example of a negative image, causing a low rating. Asymmetry in the criteria for evaluating the image of women and men by society, as well as gender imbalance among representatives with high public authority have been revealed.The boundaries of the permissible presence of women at the top of society, determined by the society itself, have been denoted. Professional areas in which women are better able to form a  positive image in the conditions of the modern information society have been noticed. It has been identified, that charity is a valuable component of a positive image of a woman in all professional fields. Traditional gender values continue to be an important component of the image. A high level of presence in the information space can contribute to image building and have negative consequences.